Identifying key areas of worklife and their interactive effect in explaining Pakistani nurses' burnout - Faisal Qadeer; Amnah Imtiaz; Imran Hameed (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2017)
We examined the effect of incongruence in the areas of worklife (AWL) on burnout of nurses. Specifically, we were interested in identifying the most important AWL and interactions among AWL and psychological resilience in explaining nurses' burnout. Incongruence in the worklife escalates burnout and resilience is a coping trait. The phenomenon needs to be studied in developing countries where entirely different health dilemmas exist. A cross sectional survey was conducted from 147 nurses. SEM through AMOS 21 and Process Macro of SPSS was used for data analysis. Two AWL namely control and reward, emerged out to be the most important factors in explaining burnout; community further mitigated reward-burnout relationship. Also, psychological resilience has a powerful independent explanatory role. Healthcare work environment must be equipped to minimize incongruence of the AWL. This congruence would need job redesigning to increase control of nurses over their jobs and reinforcement with all kinds of reward coupled with a supportive co-worker's community.
Keywords: 330; areas of worklife; burnout; nurses; resilience; Pakistan